LY2963016 Insulin Glargine and Insulin Glargine (Lantus) Produce Comparable Pharmacokinetics and Pharmacodynamics at Two Dose Levels. Issue 6 (21st September 2017) - Zhang, Xin; Lam, Eric Chen Quin; Seger, Mary E.; Coutant, David; Chua, Laiyi; Tan, Lai Hock; Soon, Danny; Linnebjerg, Helle
Abstract: LY2963016 (LY IGlar) and Lantus (IGlar) are insulin glargine products with identical amino acid sequences. This was a phase 1 single‐site, randomized, subject‐ and investigator‐blinded, 4‐treatment, 4‐period crossover study to compare the pharmacokinetic (PK) and pharmacodynamic (PD) properties of LY IGlar and IGlar at 2 different doses. Fasted healthy subjects were randomly assigned to receive 2 single doses of LY IGlar and IGlar (0.3 and 0.6 U/kg for each product). Blood samples were collected up to 24 hours postdose to assess PK, and a euglycemic clamp lasting up to 24 hours postdose was conducted to assess PD. Twenty‐four healthy subjects aged 23 to 52 years participated in the study. The primary PK parameters (area under the concentration versus time curve from 0 to 24 hours [AUC0–24 ] and maximum observed drug concentration [Cmax ]) and PD parameters (total amount of glucose infused during the clamp [Gtot ] and maximum glucose infusion rate [Rmax ]) were not statistically different between LY IGlar and IGlar at either dose. No safety concerns were noted with either drug. The study demonstrated that the PK and PD parameters for LY IGlar and IGlar were comparable following single doses at both 0.3 and 0.6 U/kg.